EMOTIONS, ARTS AND INTERVENTION: TRENDS, SYNERGIES AND PERSPECTIVES THROUGH A BIBLIOMETRIC ANALYSIS - Cantú, William Afonso; Milhano , Sandrina; Magueta, Lúcia (Revista Conhecimento Online: Diversidade e Inclusão Social, 2024)
The connection between the arts, intervention and emotions promotes reflective thinking about new ways of intervening in society to improve socio-cultural relations. This article presents an analysis that seeks to understand the intersection of the concepts of intervention, arts and emotions, helping to map the relationships and scientific developments linked to these concepts. A descriptive and exploratory study was carried out using a bibliometric analysis with performance analysis and science mapping approaches to analyze scientific production on these concepts, identifying trends, influential authors, emerging themes and collaboration networks. The results of this investigation show the potential of the research field, the thematic synergies and the multidisciplinarity involved in the research, making it possible to understand the dynamism of these concepts and the impact they have on the relationship with the 'human being'. The combination of these concepts results in scattered data and less concrete relationship networks, underlining the specificity of research in this context. Through this research, it is possible to observe broad patterns in diverse subjects such as 'human', 'performance', 'art', 'education', 'emotions', 'mental health', among others, with possibilities for future application. These results seek to open doors for further research and present the most important works, the authors and the fields of action with growth potential.